2016
DOI: 10.3233/jad-160207
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Neuroimaging Abnormalities Alone Distinguish National Football League Players from a Healthy Population

Abstract: Background: National Football League (NFL) players are exposed to multiple head collisions during their careers. Increasing awareness of the adverse long-term effects of repetitive head trauma has raised substantial concern among players, medical professionals, and the general public.Objective: To determine whether low perfusion in specific brain regions on neuroimaging can accurately separate professional football players from healthy controls.Method: A cohort of retired and current NFL players (n = 161) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 26 publications
1
43
0
Order By: Relevance
“…Perfusion imaging with SPECT in a large cohort of 161 active and retired National Football League players showed a 94% accuracy of correctly identifying individual concussed patients from healthy control subjects based on low perfusion rates in 36 frontal, temporal, parietal, and cerebellar brain regions. Areas that most contributed to the predictive accuracy included: anterior superior temporal lobes, Rolandic operculum, insula, superior temporal poles, precuneus, and the cerebellar vermis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perfusion imaging with SPECT in a large cohort of 161 active and retired National Football League players showed a 94% accuracy of correctly identifying individual concussed patients from healthy control subjects based on low perfusion rates in 36 frontal, temporal, parietal, and cerebellar brain regions. Areas that most contributed to the predictive accuracy included: anterior superior temporal lobes, Rolandic operculum, insula, superior temporal poles, precuneus, and the cerebellar vermis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have employed machine‐learning algorithms have found encouraging accuracies for: (1) identifying individual patients with recent concussions (<2 months postconcussion) from individual healthy controls; (2) identifying patients with persistent post‐traumatic symptoms (>3 months to 5 years postconcussion) from individual healthy controls; (3) classifying patients with post‐traumatic symptoms (< 5 years postconcussion) and PTSD from individuals with PTSD but without concussion history in the past 5 years; (4) identifying individual concussed patients with recent and remote concussions (months to years postconcussion) from healthy controls; and (5) for separating individual patients with PTSD from patients with TBI …”
Section: Introductionmentioning
confidence: 99%
“…2) 46,47 . Although these strain magnitudes are considered relatively low, repetitive low magnitude impact frequencies may exhibit structural and/or functional changes that are associated with long-term mental health concerns reported by current and retired football athletes 14,18,[54][55][56][57] . Further, as little as 5-15% strain levels have been associated with functional impairment of signal transmission in vitro [58][59][60][61][62] .…”
Section: Discussionmentioning
confidence: 99%
“…This has raised awareness of the link between cumulative RHI and the development and/or initiation of neurological disorders, including chronic traumatic open Scientific RepoRtS | (2020) 10:1200 | https://doi.org/10.1038/s41598-019-54874-9www.nature.com/scientificreports www.nature.com/scientificreports/ encephalopathy (CTE). CTE has been associated with exposure to RHI, and often presents with cognitive, motor and psychiatric related deficiencies [17][18][19][20] . The vulnerabilities associated with duration of exposure to RHI are implicated in a number of reports showing higher plasma tau concentrations, increased cognitive impairments and reduced microstructural integrity of the corpus callosum found in retired NFL players compared to their age matched controls 4,16,18,21,22 .Professional ASF is associated with one of the highest rates of documented concussion and the development and pathology of neurological disorder within sport 20,23,24 , and currently accounts for the greatest number of post-mortem diagnosed cases of CTE 25,26 .…”
mentioning
confidence: 99%
See 1 more Smart Citation